Improving Medication Adherence in Asthma - Kerr, Patrick J.; Brennan, Vincent; Mac Hale, Elaine; Doyle, Frank; Costello, Richard W. (Seminars in Respiratory and Critical Care Medicine, 2022)
In little over a generation, the ingenuity of scientists and clinician researchers has developed inhaled medications and pathway-specific biological agents that control the inflammation and physiology of asthma. Unfortunately, whether it is because of cost or difficulty understanding why or how to use inhaled medications, patients often do not take these medications. The consequences of poor treatment adherence, loss of control and exacerbations, are the same as if the condition remained untreated. Furthermore, poor adherence is difficult to detect without direct measurement. Together this means that poor treatment adherence is easily overlooked and, instead of addressing the cause of poor adherence, additional medicines may be prescribed. In other words, poor treatment adherence is a risk for the patient and adds cost to healthcare systems. In this article, we discuss the rationale for and the delivery of successful interventions to improve medication adherence in asthma. We contextualize these interventions by describing the causes of poor treatment adherence and how adherence is assessed. Finally, future perspectives on the design of new interventions are described.
Keywords: asthma; adherence; barriers to adherence; adherence interventions; digital inhalers; personalized care